The Relationship between Perception and Self Efficacy of Long-Acting Reversible Contraceptive (LARC) Utilization in Women's Reproductive Ages - Anindy, Maulidiyah Mahayu Nilam; Makhfudli, Makhfudli; Ni Ketut Alit Armini (Universitas Airlangga, 2022)
Introduction: LARC effectively prevents pregnancy; however, its use is still low. Self-efficacy and perception have an impact on the decision to use LARC. This study aimed to determine the relationship between perception and self-efficacy of LARC utilization in women of reproductive age. Methods: Cross-sectional study design. The population of women of reproductive age couples in the Bungah Health Center area. The research sample was 88 respondents selected by purposive sampling. The study's independent variable is the perceived benefits and perceived barriers, while the dependent variable was the self-efficacy in choosing LARC. The research instrument used a questionnaire. Statistical analysis using the Spearman's rho test with a <0,05 Results: There was a relationship between perceived benefits and selfefficacy in choosing LARC (p = 0.000) with r = 0.684. There is a relationship between the perceived barrier and self-efficacy in choosing LARC (p = 0.000) with a value of r = -0.407. Conculusion: The higher the perceived benefit, the higher self-efficacy in choosing LARC. However, if the perceived barriers are high, self-efficacy in choosing LARC will decrease. Further research needs to be done regarding other people's support factors for the choice of LARC.